Diversity of freshwater ciliates (Protista) from Argentina - Küppers, Gabriela Cristina (2016)
Diversity of ciliates from freshwater and soil were scarcely investigated in Argentina, in spite of their ecological role in these ecosystems and the huge environmental heterogeneity that can be found in this country. In the present study, we describe the morphology of nine species from a temporary pond in Buenos Aires province, by means of live observations and protargol impregnations. Stentor igneus Ehrenberg, Pseudochilodonopsis piscatoris (Blochmann), Vorticella halophila Stiller, Intranstylum invaginatum Stokes, and Epistylis rotans ?vec were recorded for the first time in Argentina, and in most cases, are new for the Neotropical realm as well. In addition, an updated checklist on freshwater ciliates from Argentina is provided, based on ciliates listed for the Salado River basin in the Buenos Aires province, new findings from Rancho Hambre peat bog pools in Tierra del Fuego province and a pond from Misiones province.